SOSIALISASI PENTINGNYA PENDIDIKAN UNTUK MEMUTUS RANTAI KEMISKINAN DAN PEMAHAMAN BAGAIMANA MENDIDIK ANAK DI ERA DIGITAL - Sudewi Sudewi; Mardiyanto Mardiyanto (LP3K Lampung, 2021)
So far, we have listened to the reality that education cannot be reached by all levels of society. Although the government has made efforts to make education friendly for the poor, without self-awareness and a change in the attitude of the family, education will be difficult to break the chain of poverty. In fact, if from an early age the children of marginalized groups are allowed to play, play, and play, and stay away from reading habits, we can see that poverty in this country will become a legacy that is difficult to maintain. In this digital era, it has changed a person's perspective in living a very sophisticated life today. A technology that makes big changes to the whole world, from helping to make things easier to creating problems due to the lack of education provided by parents so that children cannot use these increasingly sophisticated digital facilities properly and correctly. Therefore, the holding of this socialization activity aims to help parents to be more and wiser in educating children in this digital era.